ChemInform Abstract: Copper Catalyzed Oxidative Coupling of Amines with Formamides: A New Approach for the Synthesis of Unsymmetrical Urea Derivatives. Issue 46 (24th October 2013) - Kumar, G. Sathish; Kumar, R. Arun; Kumar, P. Santhosh; Reddy, N. Veera; Kumar, K. Vijaya; Kantam, M. Lakshmi; Prabhakar, S.; Reddy, K. Rajender
Abstract The presented protocol employs copper(II)bromide as catalyst for the coupling of formamides with primary‐ and secondary amines at room temperature and gives access to unsymmetrical ureas bearing different alkyl‐ or aryl substituents.